2001
DOI: 10.1111/j.1749-6632.2001.tb03539.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypofibrinogenemia Associated with a Heterozygous C→T Nucleotide Substitution at Position −1138 BP of the 5′‐Flanking Region of the Fibrinogen Aα‐Chain Gene

Abstract: We found a novel genetic abnormality, heterozygous C→T nucleotide substitution at position −1138 bp in the 5′‐flanking region of the fibrinogen Aα gene, in patients with hypofibrinogenemia. Luciferase reporter assay using the pGL3‐basic vector and CHO cells indicates that the transcriptional activity of a vector incorporated with −1138T was reduced to one‐third that of a vector incorporated with −1138C. These results suggest that the region adjacent to the −1138C bp of the 5′‐flanking region of the fibrinogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This was a heterozygous variant À1138C4T upstream of FGA identified in heterozygosity in a Japanese patient with hypofibrinogenemia [Okumura et al, 2001]. Functional analysis using a luciferase reporter gene downstream of the normal (À1138C) and mutant (À1138T) sequence suggested that the À1138T allele had significantly reduced enhancer activity (only 25% of the activity measured for the À1138C allele in HepG2 cells).…”
Section: Promoter Mutationsmentioning
confidence: 99%
“…This was a heterozygous variant À1138C4T upstream of FGA identified in heterozygosity in a Japanese patient with hypofibrinogenemia [Okumura et al, 2001]. Functional analysis using a luciferase reporter gene downstream of the normal (À1138C) and mutant (À1138T) sequence suggested that the À1138T allele had significantly reduced enhancer activity (only 25% of the activity measured for the À1138C allele in HepG2 cells).…”
Section: Promoter Mutationsmentioning
confidence: 99%
“…This seems to confirm that the Aa chain synthesis is not rate-limiting and that one normal allele is sufficient for achieving normal synthesis. Heterozygosity has been found only for the )1138c>t mutation affecting a regulatory sequence and reducing transcription [9]. The Aa Grand Lyon mutation is also present on a sole allele.…”
mentioning
confidence: 99%
“…However, this heterozygous mutation would not necessarily cause hypofibrinogenaemia even if it were to affect both alleles (i. e. trans acting). In fact, the authors who reported this mutation do not exclude the possibility that the affected individual might have a large heterozygous deletion in one of the fibrinogen genes [69].…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that any aberrant Aa chains produced would be outcompeted by the surplus of normal chains, resulting in low or no expression of these variants in the circulating fibrinogen of heterozygotes. In fibrinogen Hamamatsu, which is associated with hypofibrinogenaemia, the mutant -1138 T allele was shown to decrease a gene transcription by 35 % compared with the wild-type -1138 C allele [69]. However, this heterozygous mutation would not necessarily cause hypofibrinogenaemia even if it were to affect both alleles (i. e. trans acting).…”
Section: Discussionmentioning
confidence: 97%